The Production Of Cast Metal Matrix Composite By A Modified Stir Casting Method - Hashim, Jasmi (Penerbit UTM Press, 2001)
In a normal practice of stir casting technique, cast metal matrix composites (MMC) is produced by melting the matrix material in a vessel, then the molten metal is stirred thoroughly to form a vortex and the reinforcement particles are introduced through the side of the vortex formed. From some point of view this approach has disadvantages, mainly arising from the particle addition and the stirring methods. During particle addition there is undoubtedly local solidification of the melt induced by the particles, and this increase the viscosity of the slurry. A top addition method also will introduced air into the slurry which appears as air pockets between the particles. The rate of particle addition also needs to be slowed down especially when the volume fraction of the particles to be used increases. This is time consuming for a bigger product. This study propose a new approach of producing cast MMC. When all substances are placed in a graphite crucible and heated in an inert atmosphere until the matrix alloy is melted and then followed by a two-step stirring action before pouring into a mould has advantages in terms of promoting wettability between the silicon carbide particle and the A359 matrix alloy. The success of the incorporation of silicon carbide particles into the matrix alloy showed that the wettability between silicon carbide particles and mechanical properties such as hardness and tensile strength are comparable with previous data produced by other researchers.